Influence of alkaline metal to phase transitions in ferroelastics M₂CdI₄ (M = K, Rb, Cs) - Yunakova, O.N.; Miloslavsky, V.K.; Kovalenko, E.N. (Functional Materials, 2005)
The absorption spectrum of thin films Cs₂Cdl₄ was studied in energy interval 3.6-5.1 eV and temperatures 90-410 К at their heating and cooling. The regularities are ascertained
in behaviour of the thin films of isostructural compounds M₂Cdl₄ (M = К, Rb, Cs). With an increase of ion radius of alkali metal the temperatures of phase transitions are lowed,
the value of temperature hysteresis in spectral position and halfwidth of exciton bands is decreased, and the temperature wash-out of phase transitions is increased. We supposed that these effects are connected with increase of squeezing of structural elements Cdl₄²⁻ in crystal lattices of compounds as a result of increase of alkali metal ion radius. Исследован спектр поглощения тонких пленок Cs₂Cdl₄ в интервале энергий 3,6-5,1 эВ и температур 90-410 К при нагревании и охлаждении. Установлены закономерности в характере поведения тонких пленок изоструктурных соединений M₂Cdl₄ (M = К, Rb, Cs) вблизи температур фазовых переходов. С ростом ионного радиуса щелочного металла снижаются температуры фазовых переходов, уменьшается величина температурного гистерезиса в спектральном положении и полуширине экситонных полос и увеличивается размытие фазовых переходов по температуре. Мы предположили, что эти эффекты связаны с увеличением сжатия структурных элементов Cdl₄²⁻ в кристаллической решетке соединений, в результате роста радиуса щелочного металла. Дослiджено спектр поглинання тонких плiвок Cs₂Cd₄ в iнтервалi енергiй 3,6-5,1 еВ i температур 90-410 К при нагрiваннi й охолодженнi. Установлено закономiрностi у характерi поведiнки тонких плiвок iзоструктурних сполук M₂Cd₄l₄ (M = К, Rb, Cs) бiля температур фазових переходiв. Iз зростанням iонного радiуса лужного металу знижуються температури фазових переходiв, зменшується величина температурного гiстерезису у спектральному положеннi i напiвширинi екситонних смуг i збiльшується розмиття фазових переходiв за температурою. Ми припустили, що цi ефекти зв'язанi зi збiльшенням стиску структурних елементiв Cdl₄²⁻ у кристалiчних гратах сполук внаслiдок зростання радiуса лужного металу.